Analisis Harga Pokok Penjualan Pada Toko Sinar Kumala Elektronik Di Tenggarong - Nini Astuti; Iskandar Iskandar; Sabran Sabran (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
Abstract:one of the businesses in Tenggarong is the Sinar Kumala Electronic, which is engaged in the sale of electronic goods such as refrigerators, televisions, air conditioners and others. As for the items contained in the Sinar Kumala Electronic shop originating from the city of Samarinda, Surabaya and Jakarta.Data analysis tool that used to find out the cost of goods sold at the Sinar Kumala Electronic shop in Tenggarong by using inventory and sales data as well as repurchase of goods made. Based on the research note that the hypothesis that has been stated "that the cost of goods sold by the entrepreneur is smaller than the researcher version in May 2017" then the hypothesis proposed by the researcher is accepted and proven to be true Keyword: Cost Of Goods Sold, Full Costing